Job- and organization-based psychological ownership: relationship and outcomes - Peng, He; Pierce, Jon (Journal of managerial psychology, 2015)
Purpose – The purpose of this paper is to investigate the relationship between job- and organization-based psychological ownership. In addition, the authors explored the emergence and outcomes of psychological ownership in Chinese context. Design/methodology/approach – Time-lagged survey data from 158 Chinese participants were used to test several hypothesized relationships employing partial least square techniques. Findings – Job-based psychological ownership appeared to mediate the relationship between experienced job control and organization-based psychological ownership. In addition, a statistically significant relationship between job-based psychological ownership and job satisfaction, organizational citizenship behaviors and turnover intentions, and a statistically significant relationship between organization-based psychological ownership and job satisfaction were observed. A negative relationship between organization-based psychological ownership and knowledge withholding was also observed. Practical implications – Managers who want to enhance employees’ job- and ultimately organization-based psychological ownership should empower their employees by enabling them to exert control over their work. Originality/value – This paper examined how organization-based psychological ownership emerges from control over work via job-based psychological ownership. The authors also investigated the impact of psychological ownership in Chinese context.